2011
DOI: 10.1593/neo.11800
|View full text |Cite
|
Sign up to set email alerts
|

Functional Sphere Profiling Reveals the Complexity of Neuroblastoma Tumor-Initiating Cell Model

Abstract: Neuroblastoma (NB) is a neural crest-derived childhood tumor characterized by a remarkable phenotypic diversity, ranging from spontaneous regression to fatal metastatic disease. Although the cancer stem cell (CSC) model provides a trail to characterize the cells responsible for tumor onset, the NB tumor-initiating cell (TIC) has not been identified. In this study, the relevance of the CSC model in NB was investigated by taking advantage of typical functional stem cell characteristics. A predictive association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
76
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 69 publications
6
76
2
Order By: Relevance
“…The sphere-forming cells, selected from the highly malignant NBL tumor samples are resistant to doxorubicin, cisplatin and etoposide compared to cells cultivated in medium with serum. Average CD133 expression was also increased in spheres but not in every analyzed sphere derived from NBL samples and cell lines [56]. This finding doubts the significance of CD133 as an universal marker of all CSCs in NBL and shows that is unreliable to detect CSCs using a single marker.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…The sphere-forming cells, selected from the highly malignant NBL tumor samples are resistant to doxorubicin, cisplatin and etoposide compared to cells cultivated in medium with serum. Average CD133 expression was also increased in spheres but not in every analyzed sphere derived from NBL samples and cell lines [56]. This finding doubts the significance of CD133 as an universal marker of all CSCs in NBL and shows that is unreliable to detect CSCs using a single marker.…”
mentioning
confidence: 81%
“…Hansfrod et al examined cells isolated from bone marrow metastases and those cells form spheres regardless of the risk group. While Coulon et al used isolated cells from primary tumors that had grown as spheres only when they were derived from HR NBL [56]. 16p13.3, 19p13.3, and 19q13.33 that are absent in CD133-cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, several researchers are attempting to develop methods to reverse the chemoresistance of cancer stem cells. In this study, we developed a method to generate self-renewing and drug-resistant stem cells from the H460 cell line via sphere propagation, utilizing ultra-low-adherent substrates and growth factors such as EGF, bFGF, and B27, as described in previous studies (Coulon et al, 2011;Su et al, 2013). A number of studies have reported that cisplatin, widely used as a therapeutic agent against NSCLC, causes severe side effects (Karasawa and Steyger, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al [37] have shown that human brain tumors contain CD133+ stem-like cells that are capable of growing tumors in immune-deficient mice. Cournoyer et al [40] have shown that CD133 high neuroblastoma (NB) cells have high tumor initiating cell properties, and Coulon et al [41] suggest that CD133, ABC transporter, Wnt and NOTCH genes are sphere markers in NB cells. Overall, 19-29 % of cells in glioblastomas and 6-21 % of cells of medulloblastomas are reported to be CD133+ and tumorigenic [33].…”
Section: Cancer Stem Cells In Neuroblastoma Tumorigenicitymentioning
confidence: 99%